Exact solution of MHD mixed convection periodic flow in a rotating vertical channel with heat radiation - Singh, K.D. (Zielona Góra: Uniwersytet Zielonogórski)
Magnetohydrodynamic (MHD) mixed convection flow of a viscous, incompressible and electrically conducting fluid in a vertical channel is analyzed analytically. A magnetic field of uniform strength is applied perpendicular to the planes of the channel walls. The fluid is acted upon by a periodic variation of the pressure gradient in the vertically upward direction. The temperature of one of the plates is non-uniform and the temperature difference of the walls of the channel is high enough to induce heat transfer due to radiation.
Keywords: periodic flow; mixed convection; magnetohydrodynamical; MHD; rotating system; heat radiation